Agronomic and environmental constraints on fertilizer effectiveness - Zaman, S. M. H. (International Food Policy Research Institute, 1987)
For the average farmer in Bangladesh, the use of chemical fertilizer is most effective and profitable when he possesses technical knowledge about soil conditions, pesticides, and the importance of timing and balance in fertilizer application rates. Even small deviations from proper usage and timing of fertilizer application may result in substantially lower yields. At the national level, many field demonstrations and experiments have been done that have substantially narrowed the gap in knowledge. This paper presents many of these findings.